Influence of Heat Treatment of Steel AISI316L Produced by the Selective Laser Melting Method on the Properties of Welded Joint - Mohyla, Petr; Hajnys, Jiri; Gembalová, Lucie; Zapletalová, Andrea; Krpec, Pavel (Materials (Basel, Switzerland), 2022)
This work is focused on the influence of heat treatment of a part produced by the SLM (selective laser melting) method of stainless steel, 316L. Two heat treatment regimens were tested and compared with the state without heat treatment. Subsequently, TIG (tungsten inert gas) welds were created on the base materials processed in this way. All welds were subjected to mechanical tests and microstructural analysis. The tensile test was performed both for the welded joint and for the base material in the transverse and longitudinal directions. The tensile strength values of the samples with the welded joint were compared with the values required for the base material, 316L forged steel (1.4404). Microstructural analysis revealed significant differences between samples with and without heat treatment. The results of these tests are supported by SEM analysis. EDAX (energy dispersive analysis of X-rays) semiquantitative analysis confirmed the presence of ultra-fine pores in the structure. The results of mechanical tests show that the solution annealing at 1040 °C for 0.5 h gives better results than the same heat treatment with a duration of 2 h.
Keywords: mechanical properties; microstructural analysis; heat treatment; AISI 316L; selective laser melting; tungsten inert gas welding